A study on the effects of sintering temperature on the densification of alumina / Mohd Muslim Md. Isa - Md. Isa, Mohd Muslim (2005)
Aluminium Oxide (Al2O3), also known as alumina is an advanced ceramic material with a wide range of applications. Therefore, it is important to analyze and understand the impact of processing on its properties. In this project, alumina powder was mixed with a small amount of magnesium oxide (MgO) also know as magnesia powder. The mixture was based on 95%wt alumina powder and 5%wt magnesia powder. The mixture then pressed at 20 tons by using hydraulic press for 5 minutes and sintered at 5 different temperatures, ranging from 1500°C to 1700°C. The samples were then subjected to 3 characterization tests in order to determine the density, percentage of porosity, hardness and percentage of shrinkage. The percentage of shrinkage was determined by using a basic equation of the size ratio between before and after sintering process. Interconnected porosity was determined by using optical analyzer and 'water absorption method'. 'Water absorption test' also has been used to determine the bulk density of the samples. Hardness of the sintered samples were determine by using the Equastat hardness tester which is based on the static Rockwell measuring principle, especially suitable for hardness measurement on small parts.